Financing and collaboration on research and development for nodding syndrome. Issue 1 (December 2016) - Årdal, Christine; Røttingen, John-Arne
Abstract Background Nodding syndrome is a neurological disease with no known cure or treatment, impacting children aged 3–18 years old, mainly in East Africa. Children progressively develop varying degrees of cognitive impairment which may lead to severe wasting, a vegetative state and, eventually, death. Despite its 50-year existence, little is known about its cause, risk factors and prognosis. It is a disease where markets will not provide solutions because the patients are both too few and too poor, making it especially neglected. Open source innovation has been recommended as an approach to neglected disease research in order to maximize available funding through greater collaboration and openness to results. Nodding syndrome is a useful case to examine the relevance of open source innovation. Methods We assessed the magnitude of research related to nodding syndrome, its availability, financing and the amount of collaboration. We surveyed researchers regarding their motivations, attitudes toward open source innovation concepts and barriers to greater collaboration. Results Little research is occurring for nodding syndrome, but it is openly available and researchers are highly collaborative. The disease is largely unknown, which is partly attributed to WHO not classifying nodding syndrome as a neglected tropical disease and not including it in any formal programme. Impacted countries, particularly Uganda, demonstrate a strong degree of ownership through both authorship and research financing. Nodding syndrome researchers have been allocated a total of €5 million from 2013 to 2019 in grant funding. Annual financing, due to three new grants, doubled from 2014 to 2015. Conclusions Nodding syndrome, a disease previously ignored by the international community, is starting to receive greater attention, although financing remains modest. If infectious, a larger epidemic could take the world by surprise. Open source innovation can likely help by sharing research protocols (to avoid duplication) and early research results (to adjust to the findings of others). The existing scientists have already endorsed open source innovation, but increased financing is needed. The support of just a few high-income countries could reap a large impact.